Microbiological quality of brazilian UHT Milk and genetic biodiversity of spore-forming bacteria - Moreira, Isabella Maria Fernandes Botelho (2019)
Milk is considered a food rich in nutrients, which makes it the ideal environment for the development of a series of microorganisms. Among the milk contaminants microorganisms, which are able to form heat-resistant spores are very important, especially for dairy companies that use UHT technology. The genus Bacillus is the most associated with milk quality, and between the species of importance in the dairy industry, we can highlight Bacillus sporothermodurans. This bacterium is an aerobic mesophyll able to produce spores resistant to UHT treatment, and throughout the storage can germinate and multiply until counts close to 105 CFU∙mL-1. The objective of this study was to determine the microbiological quality of UHT milk commercialized in Brazil with a focus on the biodiversity of sporulated thermoresistant microorganisms. This work began with the evaluation of samples of UHT milk donated by seven different companies (A, B, C, D, E, F and G), of three regions of the country (South, Southeast and Midwest) over six months. For that the steps of incubation and total plate count were performed in accordance with the Ordinance no 370 of 1997 of Ministério da Agricultura, Pecuária e Abastecimento. According to this Ordinance, which establishes that the count of aerobic mesophylls can not exceed the limit of 100 CFU∙mL-1, 50,5% of the samples evaluated were out of standards. After the seven days of incubation, two heat treatments (T1: 80 oC / 10 min and T2: 100 oC / 30 min) were applied to the inactivation of the vegetative cells and evaluation of the presence of sporulates. About five colonies were isolated from each sample and submitted to phenotypic characterization to identify the presence of B. sporothermodurans. For this, the analyzes were based on Normative Instruction n° 62 of 2003 of Ministério da Agricultura, Pecuária e Abastecimento in which each purified isolate was submitted to a series of biochemical tests (Gram staining, catalase, oxidase, anaerobic growth, glucose fermentation, esculin hydrolysis, nitrate reduction and urease test). According to the test results, none of the isolates obtained was considered B. sporothermodurans. Subsequently, the Rep-PCR analysis was carried out, which allowed grouping the isolates into clusters. After choosing, randomly, the representatives of each group, considering a similarity of 90%, these were sent to the 16S rDNA sequencing and it can be observed that the genus Bacillus was found in abundance corresponding to 100% of the isolates. Within the genus Bacillus six species were identified: Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus cereus, Bacillus subtilis, Bacillus licheniformis and Bacillus velezensis. The identification of the presence of these sporulated bacteria in UHT milk samples indicates the importance of quality maintenance of raw material, the implementation of self-control programs, and the awareness of all links in the production chain in order to obtain a quality product.